Pengaruh Dosis Urea Terhadap Pertumbuhan Dan Hasil Kedelai (Glycine max L) Varietas Dena 1 Dan Devon 1 - Aditya Murtilaksono; Amarullah Amarullah; Eko Hary Pudjiwati; Nurmaisah Nurmaisah; Samjon Samjon; Eso Solihin; Haris Maulana (Fakultas Pertanian Universitas Padjadjaran, 2021)
One of the problems on soybean production in North Kalimantan is the acidic soil conditions. The use of soybean varieties that are resistant to acidic soil conditions is an alternative to overcome this problems. Dena 1 and Devon 1 soybeans were the varieties that can be grown in acid soils. In addition to the right seeds, application of fertilizer is also needed to support the growth and grain yield of soybean. This study aimed to determine the interaction between varieties with Urea dosage on growth and grain yield of soybean varieties Dena 1 and Devon 1. The experimental design of this study was factorial randomized block design with two factors. The first factor was the soybean variety which consisted of: V1 = Devon 1 and V2 = Dena 1. The second factor was the Urea fertilizer dosage which consisted of four levels: P0 = Control, P1 = 1.32 g/plant, P2 = 2.64 g/plant, P3 = 5.28 g/plant. The results showed that there were no interaction between varieties and the Urea fertilizer dosage on growth and grain yield of soybeans. However, the variety independently had a significant effect on plant height and leaf width, which was shown by the Dena1 (V2) treatment.